2021
DOI: 10.1021/acs.est.1c04693
|View full text |Cite
|
Sign up to set email alerts
|

How Does Chitosan Affect Methane Production in Anaerobic Digestion?

Abstract: The expanding use of chitosan in sewage and sludge treatment processes raises concerns about its potential environmental impacts. However, investigations of the impacts of chitosan on sewage sludge anaerobic digestion where chitosan is present at substantial levels are sparse. This study therefore aims to fill this knowledge gap through both long-term and batch tests. The results showed that 4 g/kg total suspended solid (TSS) chitosan had no acute effects on methane production, but chitosan at 8–32 g/kg TSS in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(37 citation statements)
references
References 54 publications
0
37
0
Order By: Relevance
“…Obviously, all of these reactors were dominated by Firmicutes, Bacteroidetes, Chlorof lexi, and Euryarchaeota, which are consistent with previous publications in mesophilic anaerobic digesters. 12,14 However, there are no obvious variations of the bacterial and archaeal species at the phyla level in the presence and absence of TBBPA. Thus, further explorations at genus level were conducted, with the results being shown in Figure 4.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Obviously, all of these reactors were dominated by Firmicutes, Bacteroidetes, Chlorof lexi, and Euryarchaeota, which are consistent with previous publications in mesophilic anaerobic digesters. 12,14 However, there are no obvious variations of the bacterial and archaeal species at the phyla level in the presence and absence of TBBPA. Thus, further explorations at genus level were conducted, with the results being shown in Figure 4.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Organics metabolism directly depends on the key enzyme activity in anaerobic digestion (Figure 5). 12 Figure 5a−d shows the activities of AK, CODH, ACDS, and F420, which are respectively related to the processes of acetogenesis, homoacetogenesis, acetoclastic methanogenesis, and hydrogenotrophic methanogens, in the control and TBBPA-present reactors (i.e., 0.1 and 2.0 mg/L). 15 It can be found that 0.1 mg TBBPA/L remarkably stimulated the AK activity but significantly lowered the CODH activity (p < 0.05 in the two cases, Table S5).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Under the background of growing energy demand and fossil fuel shortage, it is urgent to exploit some renewable resources, such as biomass energy. WAS contains plentiful biodegradable organics that make it possible to be adopted as the substrate for recycling various biofuels, such as diesel, alcohol, methane, and hydrogen . Among these substances, hydrogen is considered as a clean energy source, with no carbon dioxide generated in the burning process, and water is the only combustion product.…”
Section: Introductionmentioning
confidence: 99%